Robotic-assisted double-sleeve lobectomy - Qiu, Tong; Zhao, Yandong; Xuan, Yunpeng; Jiao, Wenjie (Journal of Thoracic Disease, 2017)
Double-sleeve lobectomy, which includes bronchoplasty and pulmonary arterial angioplasty, is required for certain cases of central-type lung cancer. It is usually done by open surgery or video-assisted thoracoscopic surgery (VATS). In recently, da Vinci system and robotic surgery have been applied in such complicated cases. Here we describe the details associated with robotic-assisted double-sleeve lobectomy.